KH. Djamaluddin Amien dan Pemikiran Pendididikan Tentang Pendirian Lembaga Kaderisasi Ulama di Universitas Muhammadiyah Makassar - Muhammad Ibranim; Bahaking Ramaa; Abbas; Ilham Muchtar (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
KH. Djamaluddin Amien, a notable figure in Muhammadiyah, has addressed the organization's lack of educational institutions focused on scholarship, academic excellence, and tarjih (jurisprudence selection). He established five key institutions: laboratory schools (labschools), pesantren (Islamic boarding schools), ma’had (Islamic higher education institutions), and tarjih education. This study explores his intellectual contributions and the foundational principles of these ulama (Islamic scholars) regeneration institutions at Unismuh Makassar. Using a descriptive qualitative method, the research integrates pedagogical, historical, sociological, philosophical, and anthropological perspectives. KH. Djamaluddin emphasized three core aspects for education: faith and worship to Allah SWT, humanity's responsibility as caliphs to develop and prosper the earth. These elements are critical for individual and national progress. He championed the ethos of “ulema and aristocracy,” actualized through the establishment of various institutions at Unismuh Makassar, including Labschool SMP Unismuh Makassar, Labschool SMA 1 Unismuh Makassar, Pesantren Darul Fallaah Bissoloro Unismuh Makassar, Ma’had Albirr Unismuh Makassar, and Education for Ulama Tarjih Muhammadiyah (PUTM) Unismuh Makassar. These institutions aim to cultivate scholars proficient in tarjih and contribute to advancing Islamic education in Indonesia.